Periodization of training - Haff, G. (Conditioning for strength and human performance, 2013)
Periodization of training is a concept that is widely accepted and used by coaches and sports scientists as a method for optimizing the training process. Though this concept is widely accepted, there appears to be a large degree of confusion about what periodization is and how it is appropriately applied. This is most evident in the resistance-training literature where some believe periodization is simply the manipulation of sets, repetitions, or resistance (1-3). In reality periodization is a much more comprehensive theoretical and practical paradigm in which workloads from multiple training factors are managed in order to maximize adaptation, whilst decreasing overtraining potential. For example, an athlete may engage in a periodized training plan in which resistance training, agility and sprint training, metabolic conditioning, and tactical or technical work is undertaken at varying levels of emphasis. If these factors are mismanaged or not sequenced and integrated correctly, fatigue can become excessive and overtraining can occur, which collectively decreases the potential for optimizing athletic performance, which is the primary purpose of a periodized training plan.